Bio-Based Packaging Materials from Post-Consumer Cotton Textiles - Md. Nura Alam Shiddique; Khairul Islam; Tarikul Islam; Md. Dulal Hosen; Md. Azharul Islam; Md Imranul Islam; M Mahbubul Bashar; Gajanan Bhat (Advances in Polymer Technology)
This study aims to convert cotton-based post-consumer textile waste to biodegradable paper, which not only addresses the discarding of waste but also provides a second use of cotton. The post-consumer garment made with cotton was decolorized by stripping with concentrated NaOH and hydrose. Afterwards, it was chopped, ground, and treated with NaOH solutions. The paper was prepared through a wet-laid process by mixing carboxymethyl cellulose as a binder with chopped cotton textiles. To reduce water absorbency, the uncoated paper was coated with thermoplastic polyurethane (TPU) using heat pressing technique. The surface morphology and chemical structure of uncoated pristine paper, coated paper, and TPU films were conducted using SEM and FTIR studies. The tensile strength, contact angle, air permeability, and biodegradability tests were investigated according to the standard methods. The tensile properties of the papers were increased after TPU coating, accounting well around 28% compared to the uncoated pristine paper. The elongation at the break of the coated paper was at least 40% greater than the uncoated pristine paper. The coated paper displayed a higher water contact angle of 100°, even after 10 min. The lower air permeability was observed in the coated paper due to TPU film blocking the free spaces of the paper. The TPU-coated paper exhibited a weight loss of 48.1%–59.8% after 90 days, whereas the uncoated paper was 100% decomposed after 60 days. The burning of post-consumer cotton textile waste (PCCTW) paper generated ashes resembling those of burning paper, implying clean and environmental friendly biodegradation. The papers can replace the petroleum–plastic materials and serve as food and other packaging applications.